Effect of extraction conditions on antioxidant activities of Xanthium strumarium L. sprouts extracts - Chanakul Waraporn; Maitip Jakkrawut; Bootdee Susira (E3S Web of Conferences)
This research aims to obtain the Xanthium strumarium sprouts extract with the most potent antioxidant activities. The single-factor experiments were used to extract. Factors of extraction, including temperatures (40, 50, 60, and 70°C), time (6, 8, 10, 20, and 30 minutes), and % ethanol in solvent (40, 50, 60, and 70 % EtOH), were applied in the ultrasonic assist extraction of 40°C oven-dried Xanthium strumarium sprouts 1 gram in 25 mL of solvent. Extraction yield (% yield) and % inhibition of active radical DPPH and ABTS were determined, and the correlation to varied factors was analyzed using a statistical program (SPSS). The results showed that, at low temperatures, it would give a low % yield but not affect antioxidant activities. The longer extraction time did not provide a different % yield than the shorter one. The extraction yield is a little better when 50% ethanol is used in water as a solvent and does not affect antioxidant activities. As they observe, we can conclude that the antioxidant activities of extracts do not depend on temperature, time, or % EtOH in solvents. The % inhibition of ABTS radicals is higher than that of DPPH radicals in all experiments, and it can be relied on that the active components in this extract are more polar and favorable to solute in water than EtOH.